A Study on the Perceived Value of Mobile Service Using the Contingent Valuation Method in Korea - Sangjun Nam (International Telecommunications Society (ITS), 2017)
Mobile service fee in Korea has become a concerning issue. Although numerous studies have investigated this issue, there is still a lack of studies about the factors related to the dissatisfaction of the mobile service fee. This paper investigates those issues through estimating the gap between perceived value of mobile service and the actual payment. To measure this value and identify the factors affecting it, this paper uses the contingent valuation method with double-bounded dichotomous choice approach. The empirical result shows that usage time of mobile device, the priority of handset subsidy when choosing mobile service plan, and the awareness of mobile service payment system are related to dissatisfaction of mobile service fee. Moreover, the result implies that the mobile service subscribers might be satisfied to their mobile service fee in average. This paper suggested that the regulation for curtailing the retail price of mobile service evenly might not be an effective way to relieve the dissatisfaction of the mobile service fee.
Keywords: 330